Przyrost radialny jodły pospolitej (Abies alba Mill.) w Puszczy Iłżeckiej - Bis, Ryszard; Dobrowolska, Dorota (Leśne Prace Badawcze, 2012)
A study of diameter increment of silver fir was conducted at two sites characteristic of fresh mixed broadleaved and fresh broadleaved woodland in the Iłżecka Forest in central Poland. The aim of the investigation was to follow a tree-ring width series of silver fir, with the objective of identifying the relationship between diameter increment of silver fir and climatic factors. The mean tree-ring width of 15 trees sampled in Iłżecka Forest was 2.66 mm, which is similar to the increment of fir tree rings from the Świętokrzyskie Mountains. The mean diameter increment of fir growing at the fresh broadleaved site was significantly higher than at the fresh mixed broadleaved site. Silver fir is very sensitive to harsh winters, hence after those long and severe winters in 1929, 1940, 1947, 1952 and 1956 the tree-rings were very narrow. The mean tree-ring width was higher for following periods, 1888–1962 and 1986–2005, compared with 1963–1985 when tree rings were very narrow. The process of recovery was evident from the beginning of 1980, probably due to the decrease in the SO 2 emissions. During the twentieth century, warmer temperatures and nitrogen deposition have led to an increase in diameter growth of silver fir. Diameter growth of silver fir growing in the Iłżecka Forest decreased less than it did in other regions in Poland during a general fir decline between 1971 and 1980. The better growth of fir in Iłżecka Forest supports the assertation that it is well adapted to the local environmental conditions there.